The Role of Fibroblast Growth Factor 10 Signaling in Duodenal Atresia - Jones, Matthew L. M.; Sarila, Gulcan; Chapuis, Pierre; Hutson, John M.; King, Sebastian K.; Teague, Warwick J. (Frontiers in Pharmacology, 2020)
Introduction: Duodenal atresia (DA) is a congenital bowel obstruction requiring major surgery in the first week of life. Three morphological phenotypes are described, reflecting increasing degrees of obstruction and discontinuity of the duodenum. The cause of DA is not known. Tandler’s original ‘solid cord’ hypothesis conflicts with recent biological evidence, and is unable to account for differing DA types. In humans, a genetic etiology is supported by the association between Trisomy 21 and DA, and reports of familial inheritance patterns. Interruption of FGF10/FGFR2b signaling is the best demonstrated genetic link to DA in mice, with 35–75% of homozygous knockout embryos developing DA. Purpose: This review examines the current evidence surrounding the etiology of DA. We focus on research regarding FGF10/FGFR2b signaling and its role in duodenal and other intestinal atresia. Further, we outline planned future research in this area, that we consider necessary to validate and better understand this murine model in order to successfully translate this research into clinical practice. Conclusion: Determining the etiology of DA in humans is a clinical and scientific imperative. Fgf10/Fgfr2b murine models represent current science’s best key to unlocking this mystery. However, further research is required to understand the complex role of FGF10/FGFR2b signaling in DA development. Such complexity is expected, given the lethality of their associated defects makes ubiquitous interruption of either Fgf10 or Fgfr2b genes an unlikely cause of DA in humans. Rather, local or tissue-specific mutation in Fgf10, Fgfr2b, or their downstream targets, is the hypothesized basis of DA etiology.